Final answer:
The equation y = (x + 1)(x2 + 3x + 2) is a quadratic equation. It can be solved by expanding and then simplifying it. The simplified form of the equation is y = x^3 + 4x^2 + 5x + 2.
Explanation:
The equation given is y = (x + 1)(x2 + 3x + 2). This is a quadratic equation in polynomial form. To solve it, you'd need to expand and simplify the equation.
Expand the equation: y = x(x^2 + 3x + 2) + 1(x^2 + 3x + 2)
Simplify the equation: y = x^3 + 3x^2 + 2x + x^2 + 3x + 2
Combine like terms: y = x^3 + 4x^2 + 5x + 2
So, the simplified form of the equation is y = x^3 + 4x^2 + 5x + 2.